ANALISIS GAYA KEPEMIMPINAN KEPALA DESA DALAM PELAYANAN PUBLIK DI DESA SUKAINDAH KECAMATAN SUKAKARYA KABUPATEN BEKASI - Apriyani Saadah; Dadan Kurniansyah; Lolita Deby Mahendra Putri (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze the leadership style of the Village Head in the implementation of public services in Sukaindah Village, Sukakarya District, Bekasi Regency. The research uses a qualitative method with a case study design. Data collection is carried out through interviews, observations, and documentation involving the Village Head, village officials, sub-district authorities, and the community as informants. The research analysis uses Kartini Kartono's leadership theory which reviews leadership styles based on aspects of power, authority, and ability. The results of the study show that from the aspect of power, the Village Head has carried out his authority formally, but the supervision of the apparatus and the involvement of the village apparatus in decision-making are still not optimal. From the aspect of authority, the Village Head is considered to have a good attitude, wisdom, and able to maintain harmonious working relationships, but still lacks firmness in shaping the discipline and motivation of the apparatus. Meanwhile, in terms of ability, the Village Head is considered quite capable in providing direction and solving public service problems, but coordination, supervision, and service innovation still need to be improved. Overall, the leadership style of the Head of Sukaindah Village shows quite good leadership characteristics, but it is not yet fully effective in encouraging the improvement of the quality of public services. Therefore, it is necessary to improve the aspects of supervision, firmness, coordination, and development of service innovations in order to realize more optimal public services.